Crustal imaging of the Northwest Himalaya and its foredeep region from teleseismic events. Issue 4 (3rd July 2016) - Saikia, Sowrav; Chopra, Sumer; Baruah, Santanu; Baidya, P. R.; Singh, Upendra K.
ABSTRACT: Over 450 receiver functions from 8 broadband stations located in the Indo-Gangetic plain and Northwest Himalayan region are analyzed to examine the crustal properties across the contiguous region. We identified the P-to-S phase beneath each station and estimated the crustal thickness from time delay of this phase with respect to the direct P arrival. With the help of the slant stacking technique, we determined bulk crustal chemical properties and validated our estimate of crustal thickness. The Moho was encountered in the Indo-Gangetic plain at an average depth of 33 km and thickened towards the Northwest Himalaya with the Moho depth varying from 37 to 52 km. The thickest crust matched the highest topography, which is strong evidence of the occurrence of a crustal root of the mountain range. The time domain iterative linearized inversion technique is used to invert radial receiver functions to wave velocity structures for both tectonic regimes. From the forward modelling, we found mid-crustal low-velocity layers at different patches at a depth of 10–30 km in the Northwest Himalaya region. The presence of melts may be inferred in the mid crust with high values of Poisson ratio (σ ≥ 0.260) for the stations in the Northwest Himalaya. Towards south in the Indo-Gangetic alluvium plain, we estimated a medium to higher value of Poisson ratio (0.240 ≤ σ ≤ 0.290), but velocity modelling implies absence of an intracrustal low-velocity zone around the region.